Ultra-thin V2O5 nanosheet based humidity sensor, photodetector and its enhanced field emission properties - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
We report the synthesis of V2O5 nanosheets by a simple hydrothermal method. The as synthesized V2O5 nanosheets were characterized by Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and UV-Vis spectroscopy. The humidity sensing behaviors were investigated in the range of 11-97% relative humidity (RH) at room temperature. The maximum sensitivity of 45.3%, response time of similar to 4 min and recovery time of similar to 5 min were observed for the V2O5 nanosheet based sensor. We also demonstrated the V2O5 nanosheets as an ultra-violet photodetector with a sensing response time of similar to 65 s and recovery time of similar to 75 s with a maximum photoresponsivity of similar to 6.2%. Further, we have also carried out field emission (FE) investigations of V2O5 nanosheets under a planar ``Diode'' assembly in an ultrahigh vacuum (UHV) chamber at a base pressure of similar to 1 x 10(-8) mbar. The turn on fields required to draw field emission current densities of 1 mu A cm(-2) and 10 mu A cm(-2) are found to be 1.15 V mu m(-1) and 1.72 V mu m(-1), respectively. We achieved a maximum field emission current density of 1.532 mA cm(-2) at an applied electric field of 3.2 V mu m(-1). The field enhancement factors calculated from the slope of the Fowler-Nordheim (F-N) plot are found to be 8530 and 3530 at low field and high field regions, respectively. Our results open up several avenues towards the successful utilization of V2O5 nanosheets and other metal oxide nanosheets for various nanoelectronics device applications including sensors, photodetector and flat panel displays.